The Mariana tragedy in Brazil and the role of the judiciary power before the brazilian domestic and international environmental degradation: the conflict between the Brazilian State and Federal Jurisdictions and International Law / A tragédia em Mariana no Brasil e o papel do poder judiciário perante a degradação ambiental doméstica e internacional brasileira: o conflito entre o Estado Brasileiro e as Jurisdições Federais e o Direito Internacional - Rezende, Elcio Nacur; Murta, Antonio Carlos Diniz (Revista Brasileira de Direito, 2017)
ABSTRACT This study aims to present the world with the largest Brazilian environmental tragedy and one of the largest planetary environmental disasters, namely the breaking of the dam of mining activity of tailings from Samarco companies, Vale and BHP Billiton in the city of Mariana, State Minas Gerais, which caused massive damage to the populations of several Brazilian cities, their ecosystems and, unfortunately, broke into the Atlantic Ocean causing deterioration of maritime waters. Then, the study presents the world as the prosecutor of the states of Minas Gerais and Espirito Santo (Brazilian federal states), through civil class actions, caused the judicial branches of federal states, so companies were condemned outright to form a assets exclusively for the restoration of degraded environment and to compensation for damages suffered by the affected population. However, demonstrate that federal prosecutors also acted with the same intent described in the previous paragraph, but provoking the Federal Judiciary. As a matter of fact the actions of prosecutors of Minas Gerais, Espírito Santo and Federal and the immediate and commendable injunctions concessions determining the three to deposit more than two billion reais companies (about 500 million US dollars), several NGOs (non-governmental organizations ) and citizens also filed hundreds of lawsuits for the same purpose described in the preceding paragraphs, before hundreds of local ordinances (counties) affected by toxic mud that covered more than 500 kilometers to reach the Atlantic Ocean. In this scenario, they are handled in the Judiciary of Minas Gerais, Espírito Santo and Federal simultaneously hundreds and soon thousands (perhaps, millions) of remedial actions (collective and individual) due to the same event (dam break) demanding compensation for damage suffered by individuals and by society because of individual damage (patrimonial and moral) and environmental degradation, respectively. Obviously, these demands will provide enormous diversity of judicial decisions that certainly will present the authors a ground various legal opinions, causing legal uncertainty and possibly injustices. To make matters worse, the United Nations (UN) criticized Brazil for the delay in the disclosure of adverse effects of the tragedy, underscoring the international interest in preserving the environment. Therefore, we conclude that the disjointed performance of Judicial Powers of Brazil and hinder the indispensable fair response on the social and environmental damage, it is not enough to give the planet a satisfaction at the disaster caused by mining. KEYWORDS: Mariana Tragedy; Brazilian courts; Domestic and International Law RESUMO Este estudo objetiva apresentar ao mundo a maior tragédia ambiental brasileira e um dos maiores desastres ambientais planetários, conhecido como a ruptura da barragem de mineração de rejeitos de empresas Samarco, Vale e BHP Billiton, na cidade de Mariana, Estado Minas Gerais, que causou grandes danos às populações de várias cidades brasileiras, seus ecossistemas e, infelizmente, invadiu o Oceano Atlântico causando a degradação das águas marítimas. Em seguida, o estudo apresenta ao mundo como as Promotorias dos estados de Minas Gerais e Espírito Santo, por meio de ações cíveis públicas, condenaram de imediato as empresas envolvidas para que as mesmas formassem um ativo exclusivamente para a restauração do ambiente degradado e a compensação por danos sofridos pela população afetada. A Procuradoria Federal também agiu com a mesma intenção descrita no parágrafo anterior, contundo provocando a Jurisdição Federal. De fato, as ações dos promotores estaduais de Minas Gerais, Espírito Santo e os federais resultaram em medidas liminares que determinaram o depósito imediato de mais de dois bilhões de reais das empresas (cerca de US 500 milhões de dólares). Várias ONGs (organizações não governamentais) e os cidadãos vitimados também apresentaram centenas de ações judiciais para o mesmo propósito descrito nos parágrafos anteriores, perante as centenas de pequenos distritos afetados pela lama tóxica que cobriu mais de 500 quilômetros até chegar ao Oceano Atlântico. Neste cenário, os casos são apreciados pelo Judiciário de Minas Gerais, Espírito Santo e o Federal simultaneamente, em que centenas e logo milhares (talvez, milhões) de ações corretivas (coletivas e individuais), devido ao mesmo evento (quebra de barragem), demandarão a compensação por danos sofridos por indivíduos e pela sociedade, pelos danos individuais (patrimoniais e morais) e pela degradação ambiental, respectivamente. Obviamente, estas demandas irão proporcionar uma enorme diversidade de decisões judiciais o que, certamente, irá causar aos autores incerteza jurídica e possivelmente injustiças frente às diversas opiniões jurídicas. Por último, as Nações Unidas (ONU) criticaram o Brasil pelo atraso na divulgação dos efeitos adversos da tragédia, ressaltando o interesse internacional em preservar o meio ambiente. Portanto, concluímos que a atuação desajustada dos Poderes Judiciais do Brasil dificulta a indispensável e justa compensação aos danos sociais e ambientais, e a mesma não é o bastante para a satisfação dos danos causados pela mineração. PALAVRAS-CHAVE: Tragédia em Mariana; Tribunais brasileiros; Direito Interno e Internacional